2020
DOI: 10.32870/e-cucba.v0i13.146
|View full text |Cite
|
Sign up to set email alerts
|

Ensamblaje Fitoplanctónico De La Laguna De Cajititlán, Jalisco Durante El Año 2015

Abstract: Palabras clave: Cuerpo de agua dulce, Eutrofización, Cianobacterias tóxicas, Cylindrospermopsis sp., Microcystis sp. ENSAMBLAJE FITOPLANCTÓNICO DE LA LAGUNA DE CAJITITLÁN, JALISCO DURANTE EL AÑO 2015 ENERO-JUNIO/AÑO 7/2020/NÚMERO 13/5-15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…We can see that the monitoring points located in Lake Cajititlán increase the average TSI of the whole subbasin. Lake Cajititlán has been described as one of the most polluted water reservoirs in the country, with critical eutrophication levels reported over the years [21,25,52,53]. The San Marcos Lake subbasin (Figure 6B) had an average TSI of 91.6.…”
Section: Average Tsimentioning
confidence: 99%
See 1 more Smart Citation
“…We can see that the monitoring points located in Lake Cajititlán increase the average TSI of the whole subbasin. Lake Cajititlán has been described as one of the most polluted water reservoirs in the country, with critical eutrophication levels reported over the years [21,25,52,53]. The San Marcos Lake subbasin (Figure 6B) had an average TSI of 91.6.…”
Section: Average Tsimentioning
confidence: 99%
“…In this study, ammonia was shown to be positively correlated with agricultural land, which covers 27.4% of the Verde River-Santa Rosa Dam subbasin's surface. Eutrophication has become an ongoing subject for researchers in different locations across the state of Jalisco, such as in Chapala Lake [8,22], Verde River [20,55], and Lake Cajititlán [21,25,52,53], among others; however, little effort has been made to standardize the use of a specific methodology to evaluate eutrophication in Jalisco's freshwater bodies. While eutrophication has been a relevant matter for discussion in the area, a methodological approach to consistently assess the trophic state of surface waters has not been proposed; hence, it might be hard for public and private stakeholders to allocate financial resources and prioritize remedial action plans to improve water quality.…”
Section: Average Tsimentioning
confidence: 99%
“…From this standpoint, indigenous microalgae are preferred nowadays for biorefinery and bioremediation purposes because they are already adapted to the environmental conditions prevailing in a specific geographical location [4], Chlorella sp., Scenedesmus sp., and Chlamydomonas sp. microalgae were isolated from Cajititlán Lagoon-Jalisco, Mexico-a water body with high phytoplanktonic diversity [19]. The purpose of their isolation was to develop and propose a bioprocess to reuse and valorize the energy and nutrient content of TVs through biomass and high-valuable metabolite production with sustainable use in different economic sectors.…”
Section: Introductionmentioning
confidence: 99%